2014
DOI: 10.7309/jmtm.3.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Medical students' perceptions regarding the impact of mobile medical applications on their clinical practice

Abstract: Background: Medical apps on smart devices are popular among medical students. However, the impact of medical apps on clinical practice is relatively less known.Aims: To study the prevalence of medical app usage among medical students and assess its impact on clinical practice.Method: One hundred fifty-five first year medical students of the International Medical University, Malaysia completed an anonymous questionnaire designed to explore demographic parameters, types of smart devices owned and the medical app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 6 publications
3
19
0
Order By: Relevance
“…Present study findings showed that 68% of dental and 70.45% of medical doctors are using health care apps on their smart phone. These results are in accordance with the previous studies 21,22 . This suggests that it is a global trend and practice for health care professionals to own a smart device and use medical apps to support their study and clinical sessions.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Present study findings showed that 68% of dental and 70.45% of medical doctors are using health care apps on their smart phone. These results are in accordance with the previous studies 21,22 . This suggests that it is a global trend and practice for health care professionals to own a smart device and use medical apps to support their study and clinical sessions.…”
Section: Discussionsupporting
confidence: 94%
“…Choy koh et al found in their study 22 , that majority of their study participants have positive perceptions on health care apps usage believing that, these apps were essential tools for their studies, allowing for faster and reliable access to clinical guidelines, knowledge and skill as well as helping in decision making. Several studies performed in UK and Australia among medical faculty staff and students showed similar positive attitude towards health care apps usage 18 23,24 .…”
Section: Discussionmentioning
confidence: 98%
“…[10,16] Such benefits may result in time savings and increased quality of clinical decision making. [4,17].…”
Section: Interpretation Of the Study Results In Relation To Existing mentioning
confidence: 99%
“…[1][2][3] A key group of users who grew up with the smartphone are medical students and young healthcare professionals, with as many as 90% owning a smartphone and having medical smartphone apps installed on their devices. [4,5] With students believing that mobile technologies contribute to their medical education, it remains no surprise that institutions concerned with medical education and practice are beginning to unlock this potential. [6][7][8][9] Understanding the demands of target users plays an important role in providing content congruent with their needs.…”
Section: Introductionmentioning
confidence: 99%
“…They believed that the use of smart phones by students at school could restrain them from their education and this stands as a hurdle to their academic pursuit (John & Kritsons, 2007). Koh and Wan (2014), studied medical students perceptions regarding the impact of mobile medical application on their clinical practices; through the use of questionnaire, they surveyed 155 first year medical students of the international medical university, Malaysia, about the demographic parameters, types of smart devices owned and the medical apps used, the frequency and purposes of usage of the apps and the problems encountered in using mobile devices. The study found that there is high prevalence of smart devices and medical apps usage with positive perception regarding its usage and impact on their clinical practice.…”
Section: Awareness and Use Of Smartphonesmentioning
confidence: 99%